EFFICACY OF CRESTAR, PGF2a and GnRH COMBINATION iN · TREATMENT OF POST PARTUM ANESTROUS BUFFALOES - UTAG, S G; RAGHUWANSHI, D S; VOHRA, S C; KHAN, LA; SAHATPURE, S K (The Indian Journal of Animal Reproduction, 2023)
Twelve postpartum anestrous buffaloes were divided Into two equal groups. Group I was treated with Crestar ear implant + PGF 2• + GnRH for induction of estrus. Group II served as untreated C?ntrol. In group I, estrus was induced in 100% (n=6) treated buffaloes with an average duration of 42.38±11.09 hrs Ovulation occurred in 83.33% (n=5) buffaloes of which three conceived. None of the buffaloes from control group exhibited estrus during experimental period. Intensity and the duration of induced estrus was also studied.